Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

1.(a) solve the equation $x^4-5x^3+11x^2-13x+6=0$ , given that two of its roots $p$ & $q$ are connected by the relation $3p+2q=7$

(b) solve the equation $x^4-5x^3+11x^2-13x+6=0$ which has two roots whose difference is $1$

did I need to solve these problems by taking roots $x_1,x_2,x_3,x_4$ and using the relation between roots and coefficients and the given facts. it will be then a very lengthy process.is there any alternative short process

share|improve this question
1  
Polynomials, such as these, you should always consider 1,-1,2,-2 as a chose of your roots because in most cases that I dealt with they are. If you plug in 1 as a root you see that it satisfies the condition. From there you can factor out a $(x-1)$ from the equation. –  diimension Nov 20 '12 at 5:42
3  
diimension: I think (in general) one would try all the factors of the constant term, here 6, so also 3,-3,6,-6 besides 1,-1 and 2,-2. –  coffeemath Nov 20 '12 at 5:54

3 Answers 3

Let $$f(x) = x^4 - 5x^3 + 11x^2 - 13x + 6$$ We get that $$f(1) = 1 - 5 + 11 - 13 + 6 = 0$$ and $$f(2) = 16 - 5 \times 8 + 11 \times 4 - 13 \times 2 + 6 = 16 - 40 + 44 - 26 + 6 = 0$$ Hence, we have that $$f(x) = (x-1)(x-2)(x^2 + ax + b)$$ Plugging in $x=0$, we get that $$f(0) = 2b = 6 \implies b = 3.$$ Plugging in $x=3$, we get that $$f(3) = 2(9 +3a+3) = 81-5 \times 27 + 11 \times 9 - 13 \times 3 + 6$$ This gives us that $$6a + 24 = 12 \implies a = -2$$ Hence, we have that $$f(x) = (x-1)(x-2)(x^2 - 2x+3)$$ Hence, $$f(x) = 0 \implies x = 1 \text{ or } x= 2 \text{ or }x^2 -2x+3 = 0$$ $$x^2 -2x+3 = 0 \implies (x-1)^2 + 2 =0 \implies x = 1 \pm i\sqrt{2}$$ Hence, the roots are $$x=1,2,1 \pm i \sqrt{2}$$

share|improve this answer

You can use the Rational root theorem to find rational roots and by dividing in $x-r$ where $r$ is a root you need to find the roots of a polynomial of smaller degree.

In a) I get that $r=1$ is a root, the division yields $x^3-4x^2+7x-6$ , now using the theorem again we see that $2$ is a root, dividing by $x-1$ yields a polynomial of second degree, which you know how to find roots for.

share|improve this answer
    
I agree the rational root theorem is an easier approach than the one asked for, but that wasn't the assignment. –  Ross Millikan Nov 20 '12 at 5:49
1  
@RossMillikan - I answered "is there any alternative short process" which I tooked to be the OP question –  Belgi Nov 20 '12 at 5:52

For 1) you have that $p=\frac 13(7-2q)$, so $(x-q)(x-\frac 13(7-2q))=\frac 13(x-q)(3x-7+2q)$ divides into your polynomial. Divide that in and let $q$ be a value that leaves zero remainder.

For 2) you have that $(x-p)(x-p-1)$ divides into your polynomial.

That said, the rational root theorem seems an easier approach.

share|improve this answer

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.